Analyzing social policy multiple perspectives for critically understanding and evaluating policy - O'Connor, Mary Katherine; Netting, F. Ellen (Hoboken, N.J. Wiley, 2011)
"This unique volume outlines the different frameworks of policy analysis and explains how readers can use research and critical thinking skills to understand the different models from their formation and development to implementation. Approaching the topic from an analytical and research-based perspective, the authors help readers make better, informed choices for successfully dealing with the complexities of social policy. Social workers, public administrators, nonprofit managers and upper level students of these fields will find the tools necessary for understanding how social policies are analyzed, conceived, and ultimately applied."--Provided by publisher.
An overview of social policy analysis. Necessary groundwork ; Identifying definitions and forms of policy ; Recognizing levels and scope of social policies ; Conceptualizing policy analyisis ; Conclusion ; Discussion questions -- Thinking of policy analysis as research. The role of research in guiding policy analysis ; What constitutes research? ; Focusing the policy analysis ; An expansive view of policy analysis research ; Conclusion ; Discussion questions -- Case study: Service, engagement, and volunteerism : what's the policy all about? -- Rational policy analysis. Reason and rationality ; Rational assumptions of the positivist/postpositivist paradigm ; Rational models of policy analyisis ; How to assess the degree to which an analysis approach is rational ; Conclusion ; Discussion questions -- Applications of rational policy analysis. Using the Chambers and Wedel policy/program analytical framework ; Using Jansson's six-step policy analysis framework ; Using Huttman's policy analysis model ; Using Holcomb and Nightingale's implementation analysis model ; Using Segal and Bruzuzy's questions for social welfare policy analysis ; Discussion ; Concluding remarks about rational policy analysis ; Discussion questions -- Nonrational policy analysis. Reason and nonrationality ; Nonrational assumptions of the interpretivist/constructivist paradigm ; Nonrational approaches to policy analysis ; How to assess the degree to which an analysis approach is nonrational ; Conclusion ; Discussion questions -- Applications in nonrational policy analysis. Using Stone's policy paradox approach ; Using Kingdon's policy primeval soup or garbage can approach ; Using Prigmore and Atherton's policy analysis approach ; Using Guba's policy-in-action approach ; Using an impact-analysis approach ; Discussion ; Conslusion ; Discussion questions -- Critical policy analysis. Reason in radicality ; Assumptions of the critical paradigm ; Critical approaches to policy analysis ; How to assess the degree to which an analysis approach is critical ; Conclusion ; Discussion questions -- Applications in critical policy analysis. Using Marx's historical or dialectical method ; Analyzing cultural responsiveness in policy formulation at the organizational level ; Using Lejano's normative policy analysis ; Using Moser's approach to gender policy implementation ; Using Schiele's Afrocentric framework of policy analysis ; Discussion ; Conclusion ; Discussion questions.
Keywords: Social policy